Simulation of high pressure meat pate processing - Guts, Viktor; Koval, Olha; Bondar, Svitlana (My University, 2020)
For meat pies, it is common to use mathematical models to use regression analysis. Each time there is a change in experimental data, a new mathematical model is built, which changes the number of important independent factors and the values of their degree. Therefore, the use of regression equations in the theory of modeling the processes of microbiological synthesis does not allow to obtain the required accuracy of the results and for this reason their use can not be considered satisfactory. It is presented a new method of constructing a basic mathematical model for different types of pate in the form of a differential equation. The positive thing is that the characteristics of the model retain their dimensions: the magnitude of the pressure (Pa), the duration of its action (second), the optimization parameter - the magnitude of biological pollution (CFU). It makes it possible to determine the effectiveness of inactivation of microorganisms at different hydrostatic pressures and the duration of its exposure by the magnitude of the initial biological contamination of the pate mass. A method has been developed that makes it possible, depending on the specific conditions of the technological process, to refine the optimization parameter. Для м’ясних продуктів зазвичай використовують математичні моделі для використання регресійного аналізу. Щоразу, коли відбувається зміна експериментальних даних, будується нова математична модель, яка змінює кількість важливих незалежних факторів та значення їх ступеня. Тому використання рівнянь регресії в теорії моделювання процесів мікробіологічного синтезу не дозволяє отримати необхідну точність результатів і з цієї причини їх використання не можна вважати задовільним. Представлено новий метод побудови базової математичної моделі для різних типів паштету у вигляді диференціального рівняння. Позитивним є те, що характеристики моделі зберігають свої розміри: величина тиску (Па), тривалість його дії (секунда), параметр оптимізації - величина біологічного забруднення (КУО). Це дозволяє визначити ефективність інактивації мікроорганізмів при різному гідростатичному тиску та тривалість його впливу за величиною початкового біологічного забруднення паштетної маси. Розроблено метод, що дозволяє уточнювати параметр оптимізації залежно від конкретних умов технологічного процесу.
Keywords: meat; pate; pressure; modeling; м’ясо; паштет; тиск; моделювання; кафедра технології ресторанної і аюрведичної продукції